Delphi Fuzzy Elicitation Technique in the Determination of Third Party Failure Probability of Onshore Transmission Pipeline in the Niger Delta region of Nigeria - GO Ariavie; GC Ovuworie (Journal of Applied Sciences and Environmental Management)
The Delphi technique via the expert elicitation method becomes extremely handy particularly in view of limited availability of data in determining failure probabilities of onshore transmission pipelines in the Niger Delta region of Nigeria occasioned by third party activity. Using, ten (10) experts opinion elucidated individually via email questionnaires and summarizing their responses in linguistic languages expression that were converted into failure probabilities for twelve (12) identified third part activities in the Niger Delta region of Nigeria using Fuzzy Set Theory tools. The results show that the neglect by government has the highest probability of failure of 0.1698200. @JASEM